2007
DOI: 10.1111/j.1469-7998.2007.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of the captive breeding program of the Persian wild ass

Abstract: During the last century, many species have become endangered and conservation in terms of captive breeding has been crucial for their survival. Classical management of captive species is based on recorded genealogies. However, if pedigrees are incomplete or inaccurate, it can bias the interpretation of the results obtained from analyses based on such data. In this investigation, 12 microsatellite loci were investigated to evaluate the studbook information of the critically endangered Persian wild ass, Equus he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…An inbreeding coefficient calculated from studbook data was documented only in 18% of the studies. There were only three studies reporting a significant correlation between relatedness derived from studbook data (f) and the inbreeding coefficient (F IS ) (Nielsen et al 2007;Ruiz-Lopez et al 2009) or observed heterozygosity (H o ) (Ellegren 1999). Only four studies calculated the effective population size (N e ) of the captive population.…”
Section: Study Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…An inbreeding coefficient calculated from studbook data was documented only in 18% of the studies. There were only three studies reporting a significant correlation between relatedness derived from studbook data (f) and the inbreeding coefficient (F IS ) (Nielsen et al 2007;Ruiz-Lopez et al 2009) or observed heterozygosity (H o ) (Ellegren 1999). Only four studies calculated the effective population size (N e ) of the captive population.…”
Section: Study Characteristicsmentioning
confidence: 96%
“…However, cumulative inbreeding will affect both measures. A correlation between both values is, therefore, intuitive and has been reported (Nielsen et al 2007). A comparison of both measures in a meta-analysis may provide valuable insights, but most of the hitherto published studies only mention f, even though genetic data was available.…”
Section: Management Strategiesmentioning
confidence: 99%
“…The two challenges are the paucity of data for fundamental reproductive physiology of both genders of the subspecies and the isolated pockets of individuals or small groups that must be reproductively managed to avoid inbreeding [14][15][16][17]. The present study dealt with both issues, first by assessing seasonal endocrinology and ovarian morphology of the female as well as sperm quality and cryosensitivity of males.…”
Section: Introductionmentioning
confidence: 97%
“…In fact, in captive breeding, translocation and restocking programmes, substantial efforts are made to ensure that matings between close relatives are minimized. In cases in which animals have an unknown pedigree, molecular markers can be used to create a relative ranking of degrees of relatedness (Nielsen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%